Carrier‐Selective Traps: A New Approach for Fabricating Circuit Elements with Ambipolar Organic Semiconductors. (2nd February 2017) - Ford, Michael J.; Labram, John G.; Wang, Ming; Wang, Hengbin; Nguyen, Thuc‐Quyen; Bazan, Guillermo C.
Abstract : Ambipolar polymer semiconductors and molecular additives (acting as carrier‐selective traps) can be solution processed to control ambipolar charge transport capabilities. By selecting materials with appropriate energy level offsets, unipolar n‐type or p‐type transport can be realized from a single ambipolar polymer. Efficient complementary inverters with high gain are fabricated using this approach.